State of the art and future directions - Hasseldine, J.; Evans, Chris; Pope, Jeffrey (Prospect Media, 2001)
Compliance costs simply expressed are those costs that taxpayers incur as a result of meeting their taxation obligations over and above the payment of the tax itself. The burden of the compliance costs of taxation is now widely recognized throughout many countries in the world, particularly where research studies have taken place. This understanding and acceptance of this burden has not occurred overnight, or been easily achieved. Tax authorities in several countries in the world, including the United Kingdom and New Zealand, now include compliance cost assessments (variously designated) when assessing new taxation policies or amendments. The significance of developments in this topic may be considered from two perspectives. First, the contribution of particular research studies to methodology and knowledge in the field and secondly the development of the topic in specific countries, with ensuing studies in other countries. Rather than treat these two perspectives separately, an integrated approach is adopted. The development of the topic of tax compliance costs has five main themes or phases, identification and theoretical recognition; measurement; government recognition in taxation mission statements (lip-service); effective government policy to reduce or minimize compliance costs; and continual monitoring and the use of tax impact statements.